Antioxidant and hepatoprotective activity of Nigella sativa alcoholic extract in a CCl4-induced rat - A.S. Devadhe; Dighe, Santosh; S.S. Yadav; S. B Bhawar; R D Ghogare (Creative Pharma Assent, 2025)
Background: This study investigated the antioxidant, hepatoprotective, and sedative modulatory effects of Nigella sativa alcoholic extract (NSAE) in CCl4-induced hepatotoxicity in rats. Methods: Male Wistar rats were divided into six groups (n=6): normal control, CCl4 control, silymarin (50 mg/kg), and NSAE (100, 200, and 400 mg/kg). Hepatoprotective effects were evaluated through biochemical parameters, oxidative stress markers, and histopathological examination. Results: NSAE treatment (400 mg/kg) significantly restored liver function markers, including SGOT (20.95 ± 0.52 IU/L, p = 0.033) and SGPT (28.61 ± 0.67 IU/L, p < 0.001), compared to CCl4 control. Total protein and albumin levels were normalized to 5.68 ± 0.54 mg/dL and 3.84 ± 0.48 mg/dL, respectively. Antioxidant parameters showed marked improvement with NSAE (400 mg/kg), increasing GSH (0.26 ± 0.029 µmol/mg) and CAT (30.19 ± 2.69 µg/mL) while reducing MDA (0.048 ± 0.008 µg/mL). Histopathological examination revealed significant protection against CCl4-induced hepatic and gastric tissue damage, particularly at the 400 mg/kg. Conclusion: NSAE exhibited marked hepatoprotective activity comparable to silymarin, predominantly through antioxidant mechanisms and the maintenance of hepatic tissue integrity, indicating its potential as a natural therapeutic agent for managing liver diseases. Because of its hepatoprotective and antioxidant properties, NSAE may be explored in clinical settings as a natural supplement to traditional liver disease therapies or as a prophylactic for people at risk of liver disorders.